A Mild Panic? Media Accounts of Kratom. Issue 10 (2nd October 2020) - Webb, Megan; Griffin, O. Hayden
ABSTRACT: Historically, the news media has been a primary participant in the construction of moral panics surrounding various drugs and their users. The current study utilizes the moral panic framework to depict how the media represents a drug new to the Western world: kratom. Kratom, a traditional plant-based substance from South Asia, came in to the public's view when the DEA announced its intent to emergency schedule the substance, citing a threat to public health. We use content analysis to explore how kratom and kratom use is depicted in a sample of news media articles gathered from an online source. Broadly, we find that the news media seems to report more information about the substance and less hyperbole than is typical of media reports on drugs in the past.